If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying w + 6 = 334 Reorder the terms: 6 + w = 334 Solving 6 + w = 334 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + w = 334 + -6 Combine like terms: 6 + -6 = 0 0 + w = 334 + -6 w = 334 + -6 Combine like terms: 334 + -6 = 328 w = 328 Simplifying w = 328
| (x-5)-4(x-6)=9 | | 16x^4-5x^2-11=0 | | -3.2x=8.48 | | (1/8)(5y+64)=.25(20+2y) | | 3x=-2.25 | | 334=w(w+6) | | [36]/3= | | -1-15=-3t+t | | 2g=g+5 | | [36]3= | | 6+2(3j-2)=4(1-j) | | 5x-10+3x=7+8x-17 | | x+x+2+x+4+x+6=188 | | -16t^2+484= | | 4x-x+6=3x-2+6 | | w^3-5w^2-14w=0 | | 6(4-2x)=3(4x+8) | | 12+2x=4x/4+2x | | 0=12.5x-4.9x^2 | | -(8y+3)-(-7y-7)=-2 | | -3p-4=2p | | a+3-4=-1 | | -5+13x=-6x^2 | | -9v=27 | | 48-(12)= | | 3(c-22)=2(c-6) | | r^2+2r-7=0 | | 3.7=.21w | | -12h+39=-4h-7 | | 12(4x-4)=4(12x+1) | | 40+15+0.25x=45+45+0.35x | | 8(x-6)+(-3x)=5(x-6)+3 |